LC–MS/MS method for denosumab quantitation in human serum with rapid protein digestion using immobilized trypsin. (10th September 2018) - Shida, Hiroaki; Naito, Takafumi; Shibata, Kaito; Yamada, Yasuhide; Kawakami, Junichi
Background: Proteomics-based LC–MS/MS methods using trypsin solution have some problems including ion suppression and long protein digestion times. Few practical methods to quantify denosumab in human serum have been published.Methodology: Immunoglobulins in serum were extracted using immobilized protein G. Denatured, reduced and alkylated serum samples were digested with immobilized trypsin for 14 min. A denosumab-unique peptide was identified using a Fourier transform mass spectrometer as a signature peptide. The signature peptide was quantitated with a hybrid triple–quadrupole/linear ion-trap mass spectrometer.Conclusion: A rapid and practical proteomics-based LC–MS/MS method using immobilized trypsin for denosumab quantitation in human serum was developed. The present method has an acceptable analytical performance and can be helpful for the determination of serum denosumab in clinical settings.